Pengawasan Represif Pemerintah Pusat dalam Pembentukan Peraturan Daerah - Putra Laksana, I Putu Dedy (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 4 No 1 (2019)DO - 10.24843/AC.2019.v04.i01.p11, 2019)
Constitutional Court Verdict Number 56 / PUU-XIV / 2016 have the potential to cause juridical implications in terms of carrying out control of the Regional Government. As for the purpose of this study is to analyze and find the ideal form related to the supervision of the Central Government in the formation of Regional Regulations after the issuance of the Constitutional Court Verdict Number 56 / PUU-XIV / 2016. The type of research used in this study is normative legal research. As for the implications after the issuance of the Constitutional Court Verdict Number 137 / PUU-XIV / 2016 on Central Government control in the formation of Regional Regulations namely; Contradictory to the Principles of the Unitary State, the Central Government Only has the Authority to Implement Preventive, Regional Regulations Can Only Be Applied for Judicial Review to the Supreme Court, Inhibit Central Government Policy on Deregulation, and Not in accordance with the Good Governance Principles. Whereas the conclusion is the central government can issue recommendations or recommendations to the regional government to immediately make an amendment to the regulation that is considered contrary to the provisions of the legislation higher law, public interest and decency, but if in a state of urgency the Central Government can become a defendant for judicial review of that Regional Regulation. Putusan Mahkamah Konstitusi Nomor 56/PUU-XIV/2016 berpotensi menimbulkan implikasi yuridis terutama dalam hal pengawasan pembentukan Peraturan Daerah. Adapun tujuan studi ini adalah untuk menganalisis dan menemukan bentuk yang ideal terkait pengawasan Pemerintah Pusat dalam pembentukan Peraturan Daerah pasca diterbitkannya Putusan Mahkamah Konstitusi Nomor 56/PUU-XIV/2016. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian hukum normatif. Adapun impilikasi pasca diterbitkannya Putusan Mahkamah Konstitusi Nomor 137/PUU-XIV/2016 terhadap pengawasan Pemerintah Pusat dalam pembentukan Peraturan Daerah yakni; Bertentangan dengan Prinsip Negara Kesatuan, Pemerintah Pusat Hanya Berwenang Melaksanakan Pengawasan Preventif, Perda Hanya Dapat Dimohonkan Uji Materiil/Judicial Review Kepada Mahkamah Agung, Menghambat Kebijakan Pemerintah Pusat Tentang Deregulasi, dan Tidak Mencerminkan Prinsip Good Governance. Pemerintah pusat dapat menerbitkan anjuran atau rekomendasi kepada Pemerintah Daerah untuk segera mengadakan perubahan terhadap Perda yang dianggap bertentangan dengan ketentuan Peraturan Perundang-undangan yang lebih tinggi, kepentingan umum, dan kesusilaan, namun apabila dalam keadaan mendesak Pemerintah Pusat dapat menjadi Pemohon uji materiil terhadap Perda tersebut.